Description of a Case Series of Genetic Thrombocytopenia Diagnosed in a Hematology Service of a Reference Hospital in Bogotá, Colombia Between 2000-2021 and a Narrative Review of Literature - Casas Patarroyo, Claudia Patricia; Solano Trujillo, Maria Helena; Menoyo Caballero, Gerson; Monsalve Córdoba, María Lorcy; Cuervo Lozada, Diana Marcela (Iatreia)
Introduction: Genetic thrombocytopenias (GT) are a group of diseases classically considered very rare, associated with severe bleeding, and restricted to the pediatric population. Objective: To describe the GT cases treated in the hematology service of Hospital de San José between 2000 and 2021. Methods and materials: A retrospective descriptive case series study of patients diagnosed with GT was conducted, with a univariate descriptive analysis of data (absolute frequencies, proportions, mean and median), and relevant data subsequently plotted. Results: Six cases with mutations in six genes were associated with GT. 83% of patients were female. The median platelet count at diagnosis was 30,000/µl, and bleeding phenotype was absent or mild in 50% of cases, as was the presence of macrothrombocytes. The median time to specific diagnosis was 13 years, with half of cases initially diagnosed as primary immune thrombocytopenia. One identified mutation is associated with myeloid neoplasms. Conclusions: GT can be diagnosed in the adult population; half of cases presented with a non-severe bleeding phenotype. Prompt diagnosis impacts treatment and prognosis.